Spatial Analysis of Drinking Water Quality and Environmental Sanitation on the Incidence of Diarrhea in Toddlers - Nickolas Fernando P; Mursid Raharjo; Nurjazuli Nurjazuli (Jurnal Penelitian Pendidikan IPA, 2024)
Diarrhea is a common symptom of gastrointestinal infection caused by various bacterial, viral, and parasitic organisms and is characterized by loose stools and increased frequency when infected. Sanitation factors are closely related to environmental health and can affect the level of public health. The absence of a spatial picture of areas that are vulnerable to an increase in cases of children under five years old diarrhea complicates important case finding efforts to prevent outbreaks. The purpose of the study was to spatially analyze the effect of drinking water quality and sanitation on the incidence of diarrhea in children under five years old in the Administrative City of West Jakarta in 2023. This study used a quantitative method with a Cross Sectional research design and an ecological study with a spatial approach to determine the correlation of risk factors with cases of diarrhea in children under five years old geographically. The results of the study showed that the quality of environmental sanitation between the diarrhea group in the last 3 months and the no diarrhea group in the last 3 months had a value (p value = 0.373), water quality (p value = 0.036) with PR 1.840, CTPS habits (p value = 0.100) with PR 1.509, and type of drinking water source (p value = 1.151) with PR 1.442. And the water quality variable is the most dominant factor related to the incidence of diarrhea in children under five years old  in the West Jakarta Administrative City in 2024. The results of the multivariate analysis of logistic regression with the ward conditional backward method p value = 0.32 with PR = 4.110 CI = Low 1.129 and upper 14.96 which shows that children under five years old with drinking water quality that does not meet the requirements have a 4.110 greater chance than toddlers whose drinking water quality meets the requirements in the ODF sub-district in the West Jakarta Administrative City